2009
DOI: 10.1051/epjap/2009093
|View full text |Cite
|
Sign up to set email alerts
|

OH kinetics in photo-triggered discharges used for VOCs conversion

Abstract: The kinetic of the hydroxyl radical is studied in N 2 /O 2 /H 2 O mixtures with small amounts of acetone or isopropyl alcohol (0.5 %). The radical density is measured in absolute value in the afterglow of a photo-triggered discharge, which generates an homogeneous transient nonequilibrium plasma, using a time resolved absorption measurement method. For dry mixtures, experimental results are compared to predictions of a self-consistent 0D discharge and kinetic model. It is shown that dissociation of the VOCs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Among the various methods of production of this radical, it was shown that the three-body recombination of O and H atoms is an efficient OH production process . For a phototriggered discharge (homogeneous plasma) in a mixture of dry air with 0.5% ethane, the maximum hydroxyl radical density in the afterglow was found to be equal to about 1% of the oxygen atom density produced during the current pulse. This important OH production is related to the production of H atoms following the dissociation of C 2 H 6 , and of its byproduct, through quenching processes of the nitrogen metastable states.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various methods of production of this radical, it was shown that the three-body recombination of O and H atoms is an efficient OH production process . For a phototriggered discharge (homogeneous plasma) in a mixture of dry air with 0.5% ethane, the maximum hydroxyl radical density in the afterglow was found to be equal to about 1% of the oxygen atom density produced during the current pulse. This important OH production is related to the production of H atoms following the dissociation of C 2 H 6 , and of its byproduct, through quenching processes of the nitrogen metastable states.…”
Section: Resultsmentioning
confidence: 99%
“…The photo-triggered reactor used in the present study, called "UV510", has been described in previous publications [21][22][23][24]. It allows to create an homogeneous plasma volume, V D , of 50 cm 3 , with a discharge current pulse of 60 ns for duration.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…To the best of our knowledge, far less has been done to investigate the effect of a range of supported metal oxide catalysts on the plasma-catalytic removal of low concentration acetone. The fundamental understanding of catalyst properties in the plasma-catalytic oxidation of acetone is still very limited [17,20]. It is of primary interest to screen a range of supported metal oxide catalysts to get new insights into the roles of different metal oxides and related structures in the plasma-catalytic removal of acetone and to establish a relationship between the process performance and catalyst properties.…”
Section: Introductionmentioning
confidence: 99%